2008
DOI: 10.1021/es702857s
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nanobacteria in Human Arthritic Synovial Fluid by Method Validated in Human Blood and Urine using 200 nm Model Nanoparticles

Abstract: Earlier we introduced a biosensor for the identification of nanobacteria in water drops. Here, we generalize its principle and apply it to identify nanobacteria in synovial fluid from a patient with osteoarthritis. Results indicate the prevalence of nanobacteria in the synovial fluid. The identification method is applicable to body fluids such as unfiltered human blood and urine, is independent of culturing procedures, and permits for a rapid detection of nanoparticles in liquid drops. In view of increasing cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Regardless of the aqueous phase matrix, the aggregates of hemoglobin, once dried, coated and studied by SEM, all had the same appearance. These inert structures resemble the images of nanobacteria found in diseased hearts, kidneys, and the urine of HIV patients, as well as in cancer tissue (1,3,4,(11)(12)(13)15).…”
Section: Resultssupporting
confidence: 61%
“…Regardless of the aqueous phase matrix, the aggregates of hemoglobin, once dried, coated and studied by SEM, all had the same appearance. These inert structures resemble the images of nanobacteria found in diseased hearts, kidneys, and the urine of HIV patients, as well as in cancer tissue (1,3,4,(11)(12)(13)15).…”
Section: Resultssupporting
confidence: 61%
“…Our interest in NPs was triggered by a vast amount of literature surrounding the so-called primitive life-forms known as nanobacteria (NB) that have been described as the smallest living symbionts on earth [15]–[22], with claimed implications for a number of disease processes that include Alzheimer’s disease [23], atherosclerosis [24], calciphylaxis [25], cancer [26][28], co-infection with HIV [29], ectopic calcification [22], [24], [30][37], male infertility [38], periodontal disease [39], polycystic kidney disease [40], prostatitis [41], [42], arthritis [43], [44], and renal stone formation [17][21], [45], [46]. NB have also been implicated as potential worldwide airborne pathogens [47], as potential contaminants in vaccines [48], and as infectious agents of disease transmissible through intravenous injection and other forms of inoculation [34].…”
Section: Introductionmentioning
confidence: 99%
“…They closely resembled those found in other pathological calcification diseases. [24][25][26] The attacked cells displayed abnormally, showing signs of vacuolar degeneration, membrane structural necrosis, mitochondrial swelling, etc. This indicated that the ultrastructure of the cells was severely damaged and calcifying nanoparticles and human dental pulp cells physiologic function was in disorder after the infection.…”
Section: Discussionmentioning
confidence: 99%